Rivalidade entre Torcidas de Time de Futebol: violência nos Estádios - Salim, Leonardo Alfredo [UNESP]; Lima, Luiz Augusto Normanha [UNESP] (My University, 2011)
This research reveals an understanding that football fans have about the rivalry between fans. The fans believe that their rivalry on the one hand encourages teams, but when it passes the limit becomes violence and vandalism. The fans who attend the stadium are no longer made by families and are increasingly being criminals and delinquents who ruin the spectacle of football

Esta pesquisa revela a compreensão que torcedores de futebol possuem sobre a rivalidade entre torcidas. Os torcedores acreditam que a rivalidade por um lado incentiva os times, mas quando passa do limite torna-se violência e vandalismo. Os torcedores que frequentam os estádios deixam de ser constituídos por famílias e passam cada vez mais a serem bandidos e delinquentes que estragam o espetáculo do futebol.
Rivalry between the twisted time. violence in football stadiums
Keywords: Football; Fans; Rivalry; Phenomenology; Futebol; Torcidas; Rivalidade; Fenomenologia